Effectiveness of Intratympanic Steroid Injection in Treatment of Idiopathic Sudden Sensorineural Hearing Loss - Adhikari, Sabin; Bhandari, Chhanya; Sharma, Bibek; Rijal, Niranjan; Upadhyay, Hari Prasad; Shrestha, Nishana (Journal of Bharatpur Hospital, 2025)
Background Idiopathic sudden sensorineural hearing loss (ISSNHL) is a rapid-onset condition of unknown cause, often leading to significant morbidity. Intratympanic steroid (ITS) therapy delivers high concentrations of corticosteroids directly to the inner ear while minimizing systemic side effects, making it a promising alternative or adjunct to systemic therapy. The objective of this study is to evaluate the effectiveness of ITS in improving hearing outcomes in patients with ISSNHL and to assess its safety profile. Methods A prospective observational study was conducted on 32 adult patients diagnosed with ISSNHL within 72 hours of symptom onset. Participants received ITS (dexamethasone 4 mg/ml, 0.3- 0.5 ml per injection) on every 3-4 days for a total of three sessions over 2 weeks. Hearing thresholds were measured using pure tone audiometry (PTA) at baseline and 2nd weeks post-treatment. Recovery was classified according to Siegel’s criteria. Adverse effects were recorded. Results Total of 32 patients were enrolled in the study. Complete recovery was achieved in 23 patients (71.8%), partial recovery in 8 patients (25%), and no improvement in 1patient (3.2%). No serious adverse effects were observed; minor transient discomfort was the most common complaint. Conclusions ITS is a safe and effective treatment option for ISSNHL, with a high rate of complete recovery when initiated early. These findings support ITS as a primary or salvage therapy in managing ISSNHL.